Board Game Sebagai Media Pembelajaran Rempah-Rempah Khas Indonesia Untuk Anak Sekolah Dasar - Moch. Yordan Rismarinandyo; Raden Wisnu Wijaya Dewojati; Nafik Azizah; Fikri Khoirul Umardi (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2023)
Food is a necessity for every human life. Each country or region has its own special food. Indonesia has various regions that have their own special food, or often called traditional food. Traditional food has a distinctive taste that results from various kinds of herbs and spices. Spices are one of Indonesia's largest export commodities. Indonesia has various kinds of spices which are not only useful for flavoring dishes but can also maintain health. Each of these spices has its own shape, aroma and function. To introduce the various kinds and properties of this spice, learning media are needed that are effective, easy to accept and fun. Educational Teaching Aid (APE) is one of the media used, in this study the APE used is a board game. Board games will be used as a medium to measure students' speed in recognizing and understanding various kinds of Indonesian spices. The purpose of this research is to develop effective, efficient and fun learning media to introduce Indonesian traditional plant learning materials. The research method used is quasi-experimental. The TKT level in this study was level 3. The research location was at SDN Gentan, Ngaglik, Sleman, Yogyakarta.